Overtourism in Uzungöl Trabzon, Türkiye: A Study Based on Tourist Reviews - Guzel, Melik Onur; Ay, Eşref; Çatir, Ozan (Journal of Tourism, Sustainability and Well-being, 2024)
Uzungöl is a popular natural route and a major tourist attraction in Turkey, but recently overtourism has become a major problem. With the increase in the number of visitors, rapid construction, concreting and various forms of pollution have had a negative impact on the destination of Uzungöl and its environment. The aim of this study is to reveal the evidence for the existence of overtourism in Uzungöl through visitors’ comments on online platforms and to determine in which areas overtourism is effective. In this study, which was conducted using an exploratory approach, it was observed that many visitors commented on overtourism in Uzungöl using TripAdvisor. These comments were analysed using content analysis. As a result of the analysis, it was found that visitors’ comments focused on three themes related to overtourism in Uzungöl. These are environmental, economic, and socio-cultural themes. As a result of the study, it was determined that environmental concerns are more prominent in terms of overtourism. In addition, it was understood that tourists visiting the region have a negative image in terms of overbuilding, concretisation, and unplanned urbanisation.